PENGEMBANGAN PUCI (POP UP CULTURE OF INDONESIA) SEBAGAI MEDIA MENULIS KARANGAN SEDERHANA PADA SISWA SD/MI - Eva Alviana Rahmawati (JIP Jurnal Ilmiah PGMI, 2018)
This research is a “Research & Devolepment” research with Borg&Gall development model consisting of ten stages, but in this research only until seventh step. The assessment instrument used is the rating scale sheet. This learning media is assessed by material experts, media experts, and 2 Indonesian teachers. Learning media is also responded by 28 students of grade II SD 1 Sanden through check list method. The data of quality values are in the form of quantitative data then converted into qualitative data. Quantitative data were analyzed on each aspect of the assessment. The final score is converted into qualitative feasibility product. The results of this study are: (1) The compilation of learning media PUCI (Pop Up Culture of Indonesia) with simple essay writing material. (2) Based on the assessment of material expert are Good with an average of 3.95. Based on the assessment of by media experts are Very Good with an average of 4.40. Based on the assessment of Indonesian teacher class III are Very Good with an average of 4.21. Based on the assessment of Indonesian teacher grade IV are Very Good with an average of 4.29, so this media is suitable to use in teaching processes. (3) Based on the response of 28 students of grade II SD 1 Sanden are 100% of students respond positively with an average score of 13.71. Keywords: Research & Devolepment, Media Learning, PUCI (Pop Up Culture of Indonesia), Bahasa Indonesia.